Atorvastatin treatment increases plasma bilirubin but not HMOX1 expression in stable angina patients. (September 2015) - Mirjanic-Azaric, Bosa; Rizzo, Manfredi; Jürgens, Günther; Hallstroem, Seth; Srdic, Svetozar; Marc, Janja; Cerne, Darko
Abstract Background. In vitro and animal studies indicate that statins increase heme oxygenase-1 gene (HMOX1) expression, which then, presumably, increases plasma bilirubin concentration. However, clinical confirmation that statins concomitantly increase HMOX1 expression and plasma bilirubin concentration is lacking. We hypothesized that in patients with stable angina atorvastatin therapy (20 mg/day for 10 weeks) concomitantly increases total bilirubin concentration and HMOX1 expression, as assessed non-invasively by plasma analysis. Methods. In 44 patients with stable angina plasma concentrations of total bilirubin, HMOX1 mRNA and HMOX1 protein were measured before and after the statin treatment, as well as plasma concentrations of oxidized low-density lipoprotein (OxLDL), malondialdehyde (MDA), monocyte chemoattractant protein (MCP-1) and C-reactive protein (CRP). Results. Atorvastatin treatment increased total bilirubin concentration (median 6.95 μmol/L vs. 8.55, + 23.02%; p < 0.001), but did not change plasma HMOX1 mRNA and HMOX1 protein concentrations. Plasma concentrations of OxLDL (− 31.85%, p < 0.001), MCP-1 (− 16.20%, p = 0.020) and CRP (− 7.32%, p = 0.010) were decreased but MDA was not decreased (15.32%, p = 0.107). Within subjects, increment of plasma bilirubin concentration did not correlate with the changes in HMOX1 mRNA and protein concentrations, but correlated with low-density lipoprotein cholesterol decrement (r = − 0.374, p = 0.012). Bilirubin increment did not correlate with the changes in oxidative and inflammatory markers. Conclusion. Our prospective observational trial finally confirms that atorvastatin (20 mg/day for 10 weeks) increases plasma total bilirubin concentration. However, it seems that this effect is HMOX1-independent.